Clinical Characteristics, Chest X-Ray and Laboratory Findings of COVID-19 Patients in Leona Kefamenanu Hospital on 2021 : A retrospective study - Sequeira Saldanha, Luzelia Marta (Cermin Dunia Kedokteran, 2023)
Introduction: COVID-19 can be life-threatening in older age group and those with comorbidities. This is a study on the clinical characteristics of COVID-19 patients in rural field hospitals in Indonesia. Method: A retrospective, non-experimental study on COVID-19 patients in LeonaKefamenanu Hospital, East Nusa Tenggara, Indonesia from January 2021 to December 2021. Multivariable logistic regression analysis was used to analyze the factors associated with severe COVID-19. Results: During the period, 153 patients were registered, 66 (43.1%) were male; mostly 40 to 59 years of age. The most common symptom was cough 144 (94.1%), followed by fever (n=105, 68.9%), fatigue (n=92, 60.1%), and nausea (n=80, 52.3%). Most patients had normal leukocyte, lymphocyte, and platelet counts; 17.6% of patients had hypokalemia, more frequently seen in severe cases (p<0.029). Most patients had an abnormality in their chest x-ray on admission (63.4%) and all were severe COVID-19. Multivariatelogistic regression analysis showed that age ≥60 years (OR = 8.98, 95%CI: 1.81–44.56, p =0.007) and dyspnea (OR = 16.83, 95%CI: 1.95–144.69, p =0.010) were independently associated with severe cases. Fatigue (OR = 4.606, 95%CI: 1.589–13.354, p <0.005) was also independently associatedwith disease deterioration. Conclusion: Age ≥60 years, fatigue, and dyspnea were associated with severe cases in Leona Kefamenanu Hospital, East Nusa Tenggara, Indonesia.